2016
DOI: 10.7150/thno.13725
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors Delivery using Nanoparticles with Intrinsic Passive Tumor Targeting Properties for Tumor Therapy

Abstract: Fast clearance, metabolism and systemic toxicity are major limits for the clinical use of anti-cancer drugs. Histone deacetylase inhibitors (HDACi) present these defects despite displaying promising anti-tumor properties on tumor cells in vitro and in in vivo model of cancers. Specific delivery of anti-cancer drugs into the tumor should improve their clinical benefit by limiting systemic toxicity and by increasing the anti-tumor effect. In this work, we describe a simple and flexible polymeric nanoparticle pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Multiple investigators have identified HDAC inhibitors as drugs of interest for treating cancer, including GBM [ 1 , 8 , 17 , 41 43 ]. While in vitro results have been promising, little success has been observed in vivo [ 20 , 44 , 45 ]. As a monotherapy, quisinostat and other HDIs have shown the greatest in vivo efficacy against hematological cancers [ 17 , 19 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Multiple investigators have identified HDAC inhibitors as drugs of interest for treating cancer, including GBM [ 1 , 8 , 17 , 41 43 ]. While in vitro results have been promising, little success has been observed in vivo [ 20 , 44 , 45 ]. As a monotherapy, quisinostat and other HDIs have shown the greatest in vivo efficacy against hematological cancers [ 17 , 19 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we shifted our attention to HDAC1 in our subsequent analysis. In epigenetic regulation, HDAC1 always forms a complex at the promoter region with DNA methyltransferase 3 alpha (DNMT3a, ~100 kD), which is reported to mediate DNA de novo methylation 51 . The complex blocks the binding of transcription factors and leads to gene silencing 52 , 53 .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have described the synthesis and applications for the delivery of HDACi by nanoformulations including PLGA-based NPs for the delivery of vorinostat to prostate and colorectal cancers 37 and a polyethylene oxidenorbornene macromonomer platform for the delivery of different HDACi prodrugs for mesothelioma models. 38 In another study, lipid-polymer conjugated based NPs were utilized for the delivery of two HDACi, vorinostat and quisinostat, as radiosensitizers to investigate their therapeutic potentials in xenograft models of colorectal and prostate carcinomas. 39 The studies outlined here represent the first study using polymeric starch NPs prepared using standard emulsification methods for the delivery of therapeutic drugs to breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%